Fighting Against Violent Extremist Ideology at Indonesian Universities : Strategies and Effectiveness - Fadhilah Suralaga, Zulkifli, M. Zaki Mubarak, Ahmad Tholabi Kharlie, Imam Subchi (International Journal of Advanced Science and Technology, 2020)
This paper examines srategic policies and countermeasures taken by a number of Indonesia’s universities in countering the increasing tendency of religious radicalism among university students. Several survey results have indicated a significant number of university students exposed to radicalism, which is characterized by, among others, their willingness to justify and support violent actions in the name of religion. Questions to be answered in this paper include: what are university policies in countering the extremist ideology and to what extent are the policies effective? Based on interviews, observations, and library research, the study found that a number of Indonesian universities have issued a number of preventive policies to protect students from being influenced by violent-extremismt ideologies. They include, among others, formulating regulations, reviewing learning materials of religious education and civic education, and strengthening cooperation and networks between universities, civil societies, and state agencies, in promoting moderate Islam and countering radicalism and terrorism. Some forms of countermeasures were also implemented. The study also shows that the policies undertaken by the university have so far been relatively effective in countering the violent-extremist ideology in order to protect their students.